Proposta de modelo de avaliação periódica da produtividade dos teletrabalhadores participantes do Programa de Gestão e Desempenho nas Superintendências do Patrimônio da União (SPU) - Santana, Deise Maisa Ribeiro de (2023)
As a result of the research called "Telecommuting and Productivity: Is There Influence? A study based on the Management and Performance Program (PGD) in the Superintendencies of the Union's Heritage", which highlighted the existence of a positive relationship between telework and the achievement of productivity, corroborating previous research, this document aims to present a proposal for a model of periodic evaluation of the productivity of teleworkers participating in the PGD in the units of the Secretariat of the Union's Heritage. The findings of this research were based on an analysis model from which the study questionnaire was elaborated and, after confirmation of the consistency and reliability of the model, the evaluation form to be presented was constituted. The proposition is based on the Joint Normative Instruction SEGESSGPRT/MGI nº 24, of July 28, 2023, which provides that the PGD aims, among other aspects, to promote a results-oriented management based on evidence and focused on the continuous improvement of the deliveries of the organs and entities of the Federal Public Administration.